ANALISIS PEMANFAATAN AI UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V SEKOLAH DASAR - Nisa, Vivi Afdila; Aloysius Sailuluni; M. Habibi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The advancement of Artificial Intelligence (Al) in the digital era has opened opportunities to enhance the quality of learning, particularly in developing students' reading skills at the elementary level. However, fifth-grade students still experience difficulties in understanding texts due to low reading interest and limited access to engaging learning resources. This study aims to examine the role of Al in improving reading skills, increasing students' reading interest, and supporting more effective learning processes. This research applies a qualitative approach through a Systematic Literature Review (SLR) by analyzing relevant studies from accredited national journals. The results indicate that Al contributes positively to reading development by providing adaptive learning experiences, personalized materials, and immediate feedback that support students' comprehension. Furthermore, Al enhances learning motivation and student engagement in reading activities. Nevertheless, its implementation also presents challenges, including the risk of technological dependency and reduced critical thinking if not properly guided. Therefore, the role of teachers remains crucial in directing the appropriate use of Al in learning. This study concludes that Al has strong potential to support literacy development in elementary education when integrated with suitable pedagogical strategies.